SME Governance Guidebook - International Finance Corporation (International Finance Corporation, Washington, DC, 2020)
Small and medium enterprises (SMEs) share distinctive challenges that require specific governance practices. This guidebook presents a tailored governance framework with structures, policies, and practices that mitigate the risks and support sustainable growth of business while recognizing the resource constraints typical of SMEs. The objective of this guidebook is to help SME entrepreneurs and their investors develop a highly tailored governance improvement plan to support sustainable growth of their companies. The SME governance methodology in this guidebook represents a governance innovation by tailoring specific recommendations to the evolutionary stages of SME growth: stage one: start-up; stage two: active growth; stage three: organizational development; and stage four: business expansion. This guidebook provides an international perspective - focusing on characteristics that are common to small and midsize businesses in many different countries. Guidebook is structured as follows: chapter one, SME governance: what is it? why is it important? explains what corporate governance is and how it differs for SMEs. Chapter two, SME governance framework defines the stages of growth for SMEs as well as governance-related risks and opportunities associated with each stage. Chapter three, key governance topics and leading practices takes a deep dive into select governance concepts and practices for each of the five governance topics. Appendix, SME governance action planning tool distills the key recommendations of the SME guidebook and presents them in the form of worksheets to help identify high-priority actions appropriate to your SME’s stage of growth.